THE ROLE OF CARCINOEMBRYONIC ANTIGEN IN ASSESSING THE SUCCESS OF SURGICAL TREATMENT IN COLORECTAL CANCER BASED ON STAGING - Anindya Widyasari; Betty Agustina Tambunanan; Vicky S. Budipramana (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Colorectal cancer is the third most common cancer in Indonesia. Determination of staging is needed to determine the treatment of colorectal cancer which has four stages. Carcinoembryonic Antigen (CEA) is a serological marker for monitoring colorectal cancer status, prognostic determination, monitoring of treatment success, detecting early recurrence and spreading. The purpose of this study was to determine the evaluation of successful surgical therapy in colorectal cancer by CEA examination at each stage. Descriptive observational studies were conducted using secondary data of pre and post-surgical colorectal cancer patients examined for CEA and treated at the Dr. Soetomo Hospital from January 2015 to December 2016. The samples obtained from this study were 48 patients, with the most of them at the age of 41-60 years as much as 70.83%. Females were more than males (66.67% vs. 37.33%). The most staging stage, stage 4 was as much as 43,75% followed by stage 3 as much 41.67%, the rest were stage 1 as much as 10.42%, and stage 2 as much as 4,17%. The highest decrease in CEA levels was found in stage 4 by 85%, followed by stage 2 of 53.5%, stage 1 of 43.4% and stage 3 of 33.1% but statistically only the decrease in stage 3 was significant. In stage 1, there was a difference in pre-operative CEA with a mean of 3.09 ng/mL (0.17-5.83 ng/mL) vs. post-operative with a mean of 1.75 ng/mL (0.84-3.14 ng/mL), stage 2 levels of pre-operative CEA with a mean of 3.82 ng/mL (0.15-7.48 ng/mL) vs. post-operative with a mean 1.77 ng/mL (1.46-2.08 ng/mL), stage 3 levels of pre-surgical CEA with a median of 13.85 ng/mL (1.09-71.21 ng/mL) vs. post-operative with a median 9.26 ng/mL (<0.5-68.23 ng/mL), stage 4 pre-surgical CEA levels with a median 183.77 ng/mL (0.54-2861 ng/mL) vs. post-operative with a median 27.28 ng/mL (0.51-155.10 ng/mL). There was a decrease in CEA levels from the total number of patients by 67%, whose CEA levels remained at 12% and as much as 21% of their CEA levels increased. Successful evaluation of surgical therapy in the colon and rectal cancer by CEA examination was still varied at each stage where CEA levels decreased significantly in stage 3.